Tajdiid Ta’lim Maharah Al Qira’ah Tahlil Dlarurat Adawat Al Istifham Fi Ta’lim Maharah Al Qira’ah - Rusdi Rusdi (Jurnal Alsinatuna, 2017)
Reading is one of the four language skills that have an important role in daily life. The way and characteristics of asking questions (istifham) are influential in achieving the objective of reading comprehension of a text. The use of questions (istifham) also stimulates students to understand reading texts and foster their critical thinking. All Arabic teachers, especially those who teach reading skill, should understand and master a questioning strategy to ease comprehending the text. Hopefully, this study can be used as a confirmation of theory in the fact that there is a parallel line between the theory of istifham in the teaching of reading skill, and the process of understanding the passage. Keywords: Dharuraoh, adawat al-Istifham, Ta'lim Maharatul Qiraah.